The Influence of Collaborative Learning on Students' Misconceptions about Polynomials - Maifa Munsyaila Putri; Nizlel Huda; Syaiful Syaiful; Kamid Kamid (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Misconceptions in polynomial material pose a significant issue in mathematics education, hindering students’ conceptual understanding. This study aims to examine the effect of collaborative learning on students’ misconceptions regarding polynomials in Grade XI at SMA Negeri 14 Kota Jambi. The research employed a quasi-experimental nonequivalent control-group design involving 57 students: 28 in the experimental group and 29 in the control group. The research instrument was a diagnostic test in the form of essay items, validated by subject matter experts, and administered as both a pretest and a posttest to measure misconceptions in polynomial operations, polynomial division, and the factors and roots of polynomial equations. Data were analyzed using descriptive statistics, gain scores, and an independent sample t-test. The results indicated that collaborative learning was highly effective in reducing student misconceptions. The experimental group showed a 42.3% reduction in misconception scores (from 71.29 to 41.14), while the control group experienced only a 12.2% decrease (from 70.93 to 62.24). Hypothesis testing revealed a highly significant difference (p < 0.001) with a very large effect size (Cohen’s d = 8.848). All students in the experimental group reached the low misconception category, whereas all students in the control group remained in the moderate category. Therefore, collaborative learning was proven to be more effective than conventional instruction in addressing students’ misconceptions